Enhancement of ionic conduction and mechanical properties for all-solid-state polymer electrolyte systems through ionic and physical bonding. (March 2022) - Choi, J.; Zabihi, O.; Varley, R.J.; Fox, B.; Naebe, M.
Abstract: Solid polymer electrolytes (SPEs) are receiving significant attention as the next-generation electrolyte for battery applications, owing to their excellent safety aspects and potential load-bearing capability, as opposed to conventional organic electrolytes. Here, cyclohexanedimethanol (CHDM) was used as a new solid additive which can be replaced with most common organic or plastic crystals such as succinonitrile (SN) and polycarbonate (PC) to assist dissociation of lithium salts as well as to enhance an ionic conductivity in an epoxy-based poly (ethylene glycol) diglycidyl ether (PEGDGE) electrolyte. The PEGDGE-15 wt% bis(trifluoromethane)sulfonimide lithium salt-30 wt% CHDM formulation (Li15-CHDM30), which enables the highest ion conductivities of 0.014 mS/cm and 0.2 mS/cm at 25 °C and 90 °C, respectively, with an increased Li + transference number ( t Li + ) of 0.71, was considered the optimized PEGDGE electrolyte system. This ionic conductivity at 90 °C is 13.6% and 61.7% higher than PEGDGE electrolyte systems containing 30 wt% SN (Li15-SN30) and 30 wt% PC (Li15-PC30), alongside 8.4% and 22.5% improvements in t Li + values, respectively. It is proposed that the increase in ionic conductivity was facilitated by providing multidimensional channels at the cross-linking network interface between PEGDGE and CHDM as well as protonated groups in CHDM which attract more b is(trifluoromethane)sulfonimide anion (TFSI) − anions. Interestingly, increasing the CHDM content in the optimized PEGDGE electrolyte from 10 wt% to 30 wt% increased not only the elongation at break from 6.4% to 12.9% but also the tensile strength and toughness from 3.4 to 7 MPa and from 0.12 to 0.47 MJ/m 3, respectively, which are significantly higher than those of values for Li15-SN30 and Li15-PC30 electrolyte systems. The high ductility and ionic conductivity of the Li15-CHDM30 are owing to physical bonding of CHDM via hydrogen bond and ion-dipole interactions with the resin matrix as evidenced by fourier-transform infrared (FTIR), Raman, and 7 Li-NMR spectroscopic analyses.